Assessment of direct-acting oral anticoagulants for the treatment of venous thromboembolism in cancer patients in Thai Tertiary Care Hospital - Jennis Meanwatthana; Phatcharin Mitsuntisuk (Faculty of Pharmacy, Mahidol University, 2022)
Venous thromboembolism (VTE) is an important cancer complication. Recent studies suggest direct-acting oral anticoagulants (DOACs) are possible alternatives for this population; nonetheless, there is limited evidence to support this decision in Thai cancer patients. The primary aim of this study was to measure the cumulative incidence of VTE recurrences and major bleeding among cancer patients who received DOACs that were available in Thailand. Secondary objective was to determine factors associated recurrent VTE and major bleeding. This is a retrospective cohort study conducted in tertiary care hospitals in Thailand. Data was collected from patients who had active cancer with new diagnosis of VTE and receiving approved DOACs. There were 32 cases, who received rivaroxaban, apixaban, or dabigatran, recruited to this study. We reported 4 cases (12.5%) of recurrent VTE at 6-month. There were 6 patients (18.75%), 2 patients (6.25%), and 1 patient (3.13%) with major bleeding, minor bleeding and intracranial hemorrhage, consecutively. No correlation was found between factors associated with recurrent VTE recurrence or bleeding. This study demonstrated that DOACs may be an acceptable option for preventing VTE recurrence. However, Thai population may be potentially prone to have clinically relevant bleeding. A further prospective study is warranted to draw a final conclusion in Thai cancer patients.